Bio-inspired natural fibers-derived e-skin equipped with intelligent drug-release system for advanced robustly-integrated melanoma therapy - Xinhua Liu; Yifan Fei; Boqiang Cui; Xing Chen; Jiamin Zhang; Ouyang Yue; Zhongxue Bai; Ling Wen; Huie Jiang (Collagen and Leather)
Abstract Malignant melanoma, a highly aggressive malignancy, necessitates innovative therapeutic strategies integrating biomaterial innovation with multimodal treatment modalities. Herein, we report the development of a collagen-derived bioelectronic skin (c-ADM) nanoengineered via interfacial assembly of porcine acellular dermal matrix (ADM)—a natural collagen-rich scaffold—with conductive poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) and copper sulfide nanoparticles (CuS-NPs). This hybrid system synergizes photothermal ablation, stimuli-responsive drug delivery, and electrostimulation (ES) for comprehensive postoperative melanoma management and tissue regeneration. The c-ADM platform exhibits superior mechanical robustness, enzymatic resistance, and biocompatibility, enabling real-time motion monitoring while maintaining structural integrity in dynamic physiological environments. Leveraging the photothermal efficiency of CuS-NPs, localized hyperthermia (ΔT > 40 °C) under near-infrared (NIR) irradiation induces irreversible melanoma cell apoptosis. Concurrently, laser-triggered temperature-responsive drug release enables synchronized photothermal-chemotherapy, with sustained doxorubicin release profiles at tumor sites. Notably, pH-responsive Cu2⁺ liberation from CuS-NPs facilitates intelligent functional switching: bactericidal activity at tumor microenvironment pH (5.0–6.0) and pro-regenerative effects under physiological pH (7.4) for wound healing. In vitro/in vivo assessments confirm c-ADM’s dual therapeutic efficacy including ES-enhanced cancer cell death via mitochondrial dysfunction and accelerated full-thickness skin regeneration through collagen remodeling and angiogenesis modulation. This work establishes a collagen-based bioelectronic scaffold for personalized oncological care, integrating intraoperative tumor eradication, postoperative surveillance, and adaptive tissue reconstruction. Graphic Abstract